The World Bank policy on disclosure of information, 2002. - World Bank. (Washington, D.C. : World Bank, 2002)
This statement sets out the policy of the World Bank on public availability of information held by it and sets out materials available to the public
osc 31/01/2019
Loans
Keywords: Disclosure of information